Production & Management of Crop Residues - Das, Monalisa; Das, Monalisa (International Journal of Psychosocial Rehabilitation, 2025)
Due to change in climatic conditions and an ever-increasing global population, public is constantly seeking more efficient management of agriculture -ecosystems. The existence of crops residue is an important element of management under consideration, because it represents an overwhelming amount of organic matter that can be retained in or extracted from the agricultureecosystem. It is important to address the effect of crop residues management on the agricultureecosystem linked to local climatic conditions.Crop residues, contains huge amounts of assimilated C and minerals such as NPK (nitrogen, phospohorus, potassium) that should undergo process of recycling for developing sustainable agriculture. The management of crop residues is required to serve a dual purpose, both in the face of global warming as well as food security through increased carbon sequestration. In this study, especial focus is given on the major challenges faced by agriculture sectors, the factors affecting high productivity, surplus crop density, harmful effects related to the wastage of crops, effect of temperature on crop residues, in-situ incorporation, and management techniques like water saving, increasing crop productivity, and recommendations for managing crop residues.